REPORT ON THE EXAMINATION OF RECORDS. (The Accounting Review, 1953)
Abstract This article presents a report on the balance sheet of the American Accounting Association as of December 31, 1932 and the related statements of income and expense and of changes in net worth for the General Fund and the Life Membership Fund for the year then ended. The examination was made in accordance with generally accepted auditing standards and accordingly included such tests of the accounting records and such other auditing procedures as were considered necessary in the circumstances. Following past practice, inventories of Association publications are not included in the balance sheet. The costs of publications have been charged to operations in the year of printing. The balance sheet and statements of income and expense and of changes in net worth present fairly the financial position of the American Accounting Association at December 31, 1952 and the results of its operations for the year then ended, in conformity with generally accepted accounting principles applied on a basis consistent with that of the preceding year.